(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The Roman Empire inherited the thorn of Seleucid kingdom in Syria . ( after the fall of its last king , Antiochus XIII ) . And turn Syria into one of the most important states of the Roman Empire , which lasted about seven centuries . The Romans didn’t change much the conditions that prevailed in Syria in terms of economic and social development , mainly prosperous and developed , whose prosperity was affected by wars , this prosperity which reflected in its construction and its facilities according to the economic situations of its various social classes between the rich class ( and owners and large villages ) , owners the villas and large two storey residences , the middle class with medium and small residences , and the working poor class in the small wooden cottage . This research includes a historical and geographical overview of Syria during the Roman period . and the working poor class in the small wooden cottage. It will also describe the discovered housing in the countryside and the city , as well as mention of military housing in a number of Syrian cities in north ( the calcareous plateau ) and in the south ( the Basalt region ) Horan , Palmyra , Apamea and Doura Europos .